Pengaruh Persepsi Harga, Promosi, Dan Desain Kemasan Terhadap Minat Beli Konsumen AMDK Merek ADES - Oppy Nisrina Muflihah; Heri Susanto; Dewi Fitrianti (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
ABSTRACT This study aims to determine the effect of perceived price, promotion, and packaging design on consumer buying interest in ADES brand bottled drinking water (AMDK), both partially and simultaneously. The sample used in this study was 120 respondents. The analytical method used is multiple linear regression with the dependent variable being consumer buying interest, and the independent variable being price perception, promotion, and packaging design. The results showed that promotion partially had no effect on consumer buying interest, price perceptions and packaging design had a partial effect on consumer buying interest. Perceived variables of price, promotion, and packaging design simultaneously affect consumer buying interest. Of the two influential independent variables, the packaging design variable has the greatest influence on consumer buying interest. Keywords: Perceived Price, Promotion, Packaging Design, Consumer Purchase Interest